Video-Based Multi-Agent Traffic Surveillance System - Abreu, Bruno (2013)
This paper describes Monitorix, a video-based traffic surveillance multi-agent system. Monitorix agents are grouped in four tiers, according to the kind of information processing they perform: the sensors and effectors tier, the objective description tier, the application assistant tier, and the user assistant tier. The video analysis algorithms use an adaptive, data-driven, application independent approach to extract features from the video raw data. In spite of the diversity of agent tasks, adaptive learning algorithms are used in most cases. The integration of video analysis algorithms and agent technology is made via a special middle agent called Proxy. Monitorix is a fully decentralised multi-agent system living in a FIPA Platform and using FIPA Agent Communication Language. The Tracking of vehicles across non-overlapping cameras is performed by the Tracker agent, using a traffic model and learning algorithms that tune the model parameters.